Penggunaan Maure Sipema (Media Augmented Reality – Inovasi Pembelajaran Akuntansi Mahasiswa) dalam Meningkatkan Motivasi dan Prestasi Belajar - Efni Cerya; Syamwil Syamwil; Marwan Marwan; Bagus Shandy Narmaditya; Viky Agustian; Yuriza Maulidina; Ria Susanti; Rahma Yani (Universitas Negeri Padang, 2022)
This study aims to determine the improvement in student motivation and performance by applying Maure Sipema (Media Augmented Reality - Student Accounting Learning Innovation) to the accounting materials of a manufacturing company. In this study, we employed a classroom action research (CAR) method using the four-stage Kurt Lewin model. These steps consist of planning. action; observation and reflection; My research theme is students in the first course of accounting. Test and non-test were used for data collection. The testing methodology consists of a written test at the beginning and end of each learning cycle. On the other hand, non-test techniques in the form of observational techniques, interviews and documentation during research. The analysis was based on the N-Gain-Score evaluation and was written in a qualitative descriptive format. The study was performed in 2 cycles of 5 segments. Based on Cycle I result, 72% of students completed the Maure Sipema action. Meanwhile, in Cycle II, 81% of students completed and passed the test. An open-ended questionnaire given to the students also indicated that they were more interested in participating in the lectures and more challenged to use Maure Sipema. These results highlighted the importance of innovation in learning by taking into account technological updates while also considering media compatibility with the nature of the material delivered